A DOPS e a repressão ao Movimento Estudantil em Curitiba Paraná (1964-1969) - Zaparte, Andréia (2011)
The present research seeks to understand the engenderment of institutionalized repression against the student movement in the city of Curitiba, Parana, in the period between the years 1964 to 1969, which correspond respectively to the beginning of the military dictatorship in Brazil, and the effective extinction Paranaense Union of Students (UPE) on the dissolution of its patrimony, based on the documents produced and / or archived for Delegacy of Political and Social Order (DOPS). In the context of deployment of military dictatorship, with the coup of 1964 and the National Security Doctrine, with the promulgation of Institutional Acts, Laws and Decrees, installation and strengthening of the repressive apparatus of DOPS, the student entities, then existing Were replaced by entities created by Suplicy Law (Law 4.464/64), dictatorship and tied to no autonomy. In this context, the student movement has fought favorable of the public university, free and quality education, democratic freedom and better living conditions, from dictatorship, imperialism, economic exploitation, the disruption of education in Brazil and repression. So, now considered by the political police as "internal enemies" and, consequently, were monitored and harassed, arrested and many were tortured, others have engaged the leftist movements and acted in hiding, others were killed